2016
DOI: 10.1097/olq.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sexually Transmitted Infection Case Management Services in Gauteng Province, South Africa

Abstract: Sexually transmitted infection general knowledge was suboptimal, particularly among providers without STI training. Provider training and brief refresher courses on specific aspects of diagnosis and management may benefit HIV/STI clinical care and prevention in Gauteng Province.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…This aligns with our experience in two previous studies from rural South Africa where, despite recruiting women regardless of the presence of symptoms, a relatively large proportion of women reported STI-associated symptoms upon recruitment [9,10]. Various factors may prevent symptomatic individuals from seeking health care: a lack of knowledge and awareness of sexual health and stigmatised ideas about STIs among patients and healthcare workers [11], poor effectiveness of the syndromic approach [12], lack of partner notification and subsequent reinfection [13] and rising resistance rates of N. gonorrhoeae and M. genitalium resulting in disappointment due to ineffectiveness of initial treatment [4,14].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…This aligns with our experience in two previous studies from rural South Africa where, despite recruiting women regardless of the presence of symptoms, a relatively large proportion of women reported STI-associated symptoms upon recruitment [9,10]. Various factors may prevent symptomatic individuals from seeking health care: a lack of knowledge and awareness of sexual health and stigmatised ideas about STIs among patients and healthcare workers [11], poor effectiveness of the syndromic approach [12], lack of partner notification and subsequent reinfection [13] and rising resistance rates of N. gonorrhoeae and M. genitalium resulting in disappointment due to ineffectiveness of initial treatment [4,14].…”
Section: Introductionsupporting
confidence: 88%
“…Also, perceptions, beliefs and stigma related to sexual health contribute to the burden of untreated STIs. Community education and disclosure support are needed to (15) raise community awareness, tackle common myths and alter attitudes towards sexual health [11,24]. Sexuality education for healthcare workers should address recognition of STIs, possible (non-sexually transmitted) causes, complications if left untreated and opportunities for treatment including the role of partner notification.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest knowledge of correct regimens is a problem. In the 2002 survey, 41% of providers reported knowledge of correct syndromic treatment,11 and in a 2009 study, 40% of public health providers correctly identified the recommended first-line or alternative treatment regimens for MUS and 6% for VDS 16. A more recent study found 31% of providers post training prescribed the correct syndromic regimen to patient actors, however was more conservative in including errors in dose or frequency as well as drug name 25.…”
Section: Discussionmentioning
confidence: 99%
“…Missed opportunities for referral and integration with other HIV services,13 and concerns about provider attitudes towards clients with or at risk for STIs, have been described 11 14. Previous studies of public health facilities and providers in South Africa have demonstrated stockouts, lack of provider knowledge and limited referral processes 11–13 15 16…”
Section: Introductionmentioning
confidence: 99%
“…2 Many studies have demonstrated the positive impact of SM on the incidence of STIs and HIV in a given population, but the knowledge of the SM guidelines amongst doctors is suboptimal, especially amongst those without formal STI training. 10 There is also evidence that doctors do not always adhere to national treatment guidelines. 11 This study sought to determine the knowledge, attitudes and practices of doctors regarding syndromic STI management guidelines at Jubilee Hospital.…”
Section: Introductionmentioning
confidence: 99%